Single-parenthood among migrant children: Determinants and consequences for educational performance - Jaap Dronkers; Matthijs Kalmijn (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
In this paper we address both the occurrence of single-motherhood among migrant mothers in OECD countries and the effect of living in a single-mother family on the math scores of 15-year old migrant pupils in OECD countries. We use the PISA 2009 data with an international comparative perspective, which contains 14,794 migrant pupils coming from 54 origin countries (grouped into 13 origins regions) and living in 15 OECD destination countries. We select only two-parent families and single-mother families for this analysis. Pupils have a higher risk of living in a single-mother family when one parent was born in the destination country, when they speak the destination language at home, and when they have a low socio-economic status. The risk of single parenthood also coincides with the prevalence of single parenthood in the origin country but does not reflect the prevalence of single parenthood in the destination countries. After controlling for mothers' socio-economic status and migration history, migrant pupils from single-mother families score 4 point lower on the math test than migrant pupils who live with both parents. This effect does not depend on the prevalence of single parenthood in the origin or the destination country.
Keywords: 330